2021
DOI: 10.3390/ma14164748
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structural and Magnetic Properties of Fe-Co Wire-like Nanochains Caused by Annealing Atmosphere

Abstract: Thermal treatment is a post-synthesis treatment that aims to improve the crystallinity and interrelated physical properties of as-prepared materials. This process may also cause some unwanted changes in materials like their oxidation or contamination. In this work, we present the post-synthesis annealing treatments of the amorphous Fe1−xCox (x = 0.25; 0.50; 0.75) Wire-like nanochains performed at 400 °C in two different atmospheres, i.e., a mixture of 80% nitrogen and 20% hydrogen and argon. These processes ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Both experimental and computational investigations on 1D magnetic chains have confirmed that they exhibit enhanced remanent magnetization (in the direction of the long axis), clearly distinct from the properties of individual magnetic nanoparticles. [41][42][43][44][45][46] Despite their potential as desirable anisotropic magnetic fillers in high-force-density actuators, the microscale arrangements and collective magnetic behaviors of 1D magnetic chains in a polymer matrix are yet to be investigated in great detail.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and computational investigations on 1D magnetic chains have confirmed that they exhibit enhanced remanent magnetization (in the direction of the long axis), clearly distinct from the properties of individual magnetic nanoparticles. [41][42][43][44][45][46] Despite their potential as desirable anisotropic magnetic fillers in high-force-density actuators, the microscale arrangements and collective magnetic behaviors of 1D magnetic chains in a polymer matrix are yet to be investigated in great detail.…”
Section: Introductionmentioning
confidence: 99%